Incidence, prevalence, pathogenesis, and manifestations of toxic megacolon - Almottowa, Hisham Abdullah; Alobaidi, Ahmed Eisa; Assiri, Mohammed Hadi; Almulhim, Abdullah Abdulmohsen; Aljafri, Elaf Mohammed Hameed; Alharbi, Talal Mohammed; Alrowaidan, Faisal Fahad; Alkhamis, Haya Abdulaziz; Alshammari, Mariam Hadi; Hasan, Yusra Fadhel; Qutub, Khulud Yousef; Alzahrani, Fayez Ali (International Journal Of Community Medicine And Public Health, 2022)
Toxic megacolon is an inflammatory condition that affects the colon, leading to nonobstructive dilatation and serious morbidity. It can be found as total and segmental. In the present literature review, we have discussed the epidemiology, pathogenesis, and manifestations of toxic megacolon based on relevant data from studies in the literature. Unfortunately, reports regarding the prevalence and incidence of toxic megacolon are scarce. Therefore, it is difficult to draw a suitable conclusion in this context, and further studies are encouraged. Nevertheless, infection with Clostridium difficile might be the commonest etiology, and estimates indicate that this is a significant risk factor for developing the condition. In addition, colonic motility is usually inhibited by the significant presence of certain inflammatory mediators. Furthermore, the clinical manifestations of toxic megacolon are not very specific, and the diagnosis can be made through adequate history taking, together with clinical and radiological manifestations. Finally, prompt management of the condition is essential to intervene against the development of serious complications.